Prescribed medical cannabis in women with gynecologic malignancies: A single-institution survey-based study - Emily M. Webster; Ghanshyam S. Yadav; Stefan Gysler; Blair McNamara; Jonathan Black; Joan Tymon-Rosario; Burak Zeybek; Chanhee Han; Christopher K. Arkfeld; Vaagn Andikyan; Gulden Menderes; Gloria Huang; et al. (Elsevier, 2020)
Research within a gynecologic oncology population has lagged behind the uptake in use of medical cannabis for symptom control. This study seeks to evaluate patient experience with prescribed medical cannabis obtained through licensed dispensaries in women with gynecologic malignancies.A 43-item survey exploring patient experience with medical cannabis was administered to women with gynecologic malignancies who used medical cannabis prescribed by a gynecologic oncologist.Thirty-six eligible patients were approached for consent, and 31 patients returned completed surveys (86%). Ninety-three percent had advanced or recurrent disease; 74% were receiving chemotherapy or immunotherapy. Eighty-three percent reported medical cannabis provided relief from cancer or treatment-related symptoms including decreased appetite (41%), insomnia (41%), neuropathy (41%), anxiety (35%), nausea (29%), joint pain (29%), bone pain (29%), abdominal pain (25%), and depression (19%). Eighty percent of patients reported medical cannabis worked the same or better than other traditional medications for management of their cancer or treatment-related symptoms, and 83% reported medical cannabis had an equivalent or better side effect profile. Of the subset of patients using medical cannabis for pain, 63% reported a reduction in opioid use.Patients perceive that medical cannabis was useful for relief of cancer and treatment-related symptoms, suggesting medical cannabis may be a reasonable alternative or adjunct therapy. Medical cannabis was well tolerated and may have the potential to improve neuropathic pain and decrease opioid use.